Habitat use and spatial behaviour in the European rabbit in three Mediterranean environments - Lombardi, Ludgarda; Fernández, Néstor; Moreno, Sacramento (Basic and Applied Ecology, 2007)
The abundance and behaviour of mammalian prey species such as the European rabbit (Oryctolagus cuniculus) are known to be regulated by the availability of both food for maintenance and reproduction and shelter for protection against predators and harsh weather. However, the effect of vegetation structure and temporal variations in food availability on habitat selection and spatial behaviour are still poorly understood. The present study investigated the relationship between rabbit spatial ecology and vegetation structure and food quality and quantity in three neighbouring areas in SW Spain that differed in the distribution and amount of refuge sites and food patches. In all, 35 rabbits were radiotracked in the three study areas and home range and core area sizes in different seasons and at different times of the day estimated. Spatial behaviour was then compared with parameters of vegetation cover and food quantity and quality. Lastly, rabbit habitat selection at two levels was studied: home range selection and selection within home ranges. Home range size varied from one study area and season to another, but was not dependent on either sex or the availability or quality of food. We suggest that differences in home range size between study areas respond to differences in vegetation cover, with smaller home ranges in areas with higher proportion of sheltering vegetation. It was found that habitat selection patterns varied between the three areas in terms of the need for rabbits to exploit to a maximum the scarcest resource in each situation, thereby optimising access to both feeding and refuge patches. This pattern was manifest at the home range level of habitat selection but not at the level of selection within home ranges. Findings were consistent with the high behavioural plasticity of the European rabbit in its native habitats and provide useful information for habitat management.
Keywords: Doñana National Park; Food quality; habitat selection; Home range size; Mediterranean ecosystems; oryctolagus cuniculus; predation risk; Prey behaviour; Resource availability